Content validity of Building Information Modelling (BIM) assessment criteria for framework formation for local government authorities / Muhammad Ashrof Arifuddin Zakaria, Thuraiya Mohd and Nor Asma Hafizah Hadzaman - Zakaria, Ashrof Arifuddin; Mohd, Thuraiya; Hadzaman, Nor Asma Hafizah (Universiti Teknologi MARA, Perak, 2024)
Assessment of Building Information Modelling (BIM) implementation for local government authorities is defined as a process of managerial evaluation tools that measures the organisation's assessment gap. For assessing the current quality, competence, and repeatability of BIM implementation, assessment criteria are therefore crucial. The construction industry in the country is predominantly reliant on traditional methods, hindering development and global competitiveness. Despite various initiatives to promote BIM, its adoption among construction professionals in Malaysia remains limited. To address this, the research aims to establish BIM assessment criteria tailored for local governance authorities, thereby facilitating smoother BIM implementation. The study employs literature review and questionnaire survey methods to assess the content validity of BIM assessment criteria. The data was analysed descriptively in Microsoft Excel using Content Validity Ratio (CVR) and Content Validity Index (CVI) formula. A set of questionnaires has been distributed to six (6) experts in BIM. The literature review proposes 51 items across seven main categories for inclusion in the BIM assessment criteria. The CVR scores indicate that 29 out of the 51 items are considered highly critical by content experts. additionally, item Level Content Validity Index (I-CVI) and Modified Kappa Coefficient findings reveal that 41 items demonstrate appropriateness and excellence. In conclusion, this study contributes valuable insights for the development of a BIM assessment criteria framework specifically tailored for local governance authorities. The finding of this study is beneficial for further study in developing the BIM assessment criteria framework for local governance authority.